Access to Justice: New Right or a Reaffirmation of Existing Human Rights for Persons with Disabilities? - Zengeta, Melaku T (Yustisia, 2022)
The Convention for the Rights of Persons with Disabilities (CRPD), as a specific human rights instrument, seems to create a new disability-specific right to access justice under Article 13. This study analyzed the place of specific rights for people with disability to access justice in the CRPD. The article uses the conceptual approach related to the disability and human right at the international instrument. This study concludes that Article 13 of the CRPD has expanded the traditional conceptions of access to justice since it also covers effective remedy and fair hearing. Several inherent limitations, or impairments, which interact with multidimensional and inherent barriers, have prevented persons with disabilities from accessing justice based on equality. The article has shown that the new set of rights is a guarantee of justice.